O papel do jornalismo cultural no percurso da dançateatro no Brasil: a replicação do Meme Pina Bausch - Petreca, Paula Carolina (2008)
The German choreographer Pina Bausch has had her work diffused thanks to the contribution of cultural journalism, legitimizing its assimilation into symbolic systems which compose Brazilian cultural assembly. The phenomenon performed by cultural journalism between the first two Bausch s Brazilian tours, occurred in 1980 and 1990 respectively, the first being a pale episode as the audiences reception has been cold and critical, while the second has elevated the German company to a greater level of recognition. What happened meanwhile that promoted such a change? The hypothesis is that the diffusion of information operated by press has dealt to a better knowledge of the choreographer s work, as well as turning it to be familiar to local cultural production, dealing to the construction of a context which is being under process for more than two decades. Reflections raised by Critical Theories of Communication, according to the following authors: Benjamin (1936), Baudrillard (1995), Jameson (1998) and Bauman (2001); evoke arguments which contextualize the cultural compreension of the environment that hosts the object of this research, and the object (the action of cultural journalism between 1980 and 1990 over the diffusion of information about Pina Bausch) focus on the scope of multitude s speech (Negri, 2005). The research over material published in two newspapers from São Paulo: O Estado de São Paulo e Folha de São Paulo, has been related to testimonials of various Brazilian choreographers who recognise that the information brought by Pina Bausch has transformed and impacted their work. The methodology applied has enabled the delimitation of the role played by the newspapers previously mentioned, while interchanging information between public and artists. Theoric-practical transit has been estabilished while interviewing local choreographers whose production relate in a certain way to Pina Bausch s one, that have argumented over this issue. Regarding the lack of specific conjunctural historic source concerning dance in Brazil, this dissertation aims to contribute to on-course discussions over cultural journalism impact and its traces in Brazilians dance